Defining mechanisms that determine the levels of drug resistance in Mycobacterium tuberculosis - Bester, Margaretha (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2009.